Sistem Informasi Pengelolaan Data Siswa Berbasis Web Pada SMK Negeri 1 Lolowa’u - Sibero, Alexander F.K; Dian Ayu Putriani Laia; Rianto Sitanggang; Immanuel H G Manurung (Universitas Sari Mutiara Indonesia, 2023)
In the current era of globalization, the world of information is developing so rapidly because it is supported by technological developments that are increasingly developing and sophisticated. The computer is one tool that is used to support the development of technology that information. The student data information system is very important for a school organization and other parties who need student data. We can find out about student data information effectively and efficiently. In this study the authors designed and built a system that can process student data at SMK Negeri 1 Lolowa'u Web-based with MySQL database. The tool used by the author in designing and modeling data processing information systems at SMK Negeri 1 Lolowa'u is to use the Unified Modeling Language (UML) while the programming language that the author uses is Hypertext Preprocessor or often known as PHP. The result of this research is the formation of a student data processing information system that is used to assist SMK Negeri 1 Lolowa'u, in the process of storing, collecting, and processing student data.